MASYARAKAT PEDULI LINGKUNGAN - Hasibuan, Armyn (Jurnal at-Taghyir, 2019)
Humans as the caliph of Allah Almighty means that God's representatives govern, lead and prosper the planet earth as a means of supporting devotion to the grantor of the caliph's mandate. Humans are given over the earth as a place of residence and fun with a limited time (Q.S 2: 36). So the earth is essentially a mandate that must receive the care and maintenance of mansuia as the recipient of the mandate. For this purpose, humans are equipped with various abilities by giving them potentials called hidayah.Hidayah, among others hidayah wujudiyah (existential), hissisiyah (five senses), akliyah (reason) and diniyah (religion). With a human mind that is able to imitate some of God's attributes so that he can be called The Second Creater (Second Creator). In him there is also an instinct to make him able to feel and work. As creatures of human culture are also social beings who do not live without friends and are accompanied. He must care about friends, the environment and its existence both personally and collectively can not escape from the environment. People who don't care about the environment are people who don't know who they really are.